STUDENTS’ ANXIETY IN FOREIGN LANGUAGE LEARNING ENVIRONMENTS: ONLINE VERSUS ON-SITE CLASSROOMS - Mouffok, Khadidja; Hamzaoui-Elachachi, Hafida; Omari, Fatima Zohra Imane (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
As the world continued to grapple with the pandemic of COVID-19, Algerian universities had enforced a transition to a blended teaching approach, requiring both teachers and students to adapt. Accordingly, third-year Licence chemistry students received online and on-site lectures among which English for Specific Purposes lectures. This sudden transition from face-to-face to online teaching had an effect on university students namely at the emotional level which led this research to investigate the impact of both modes of course delivery on students’ affective filter specifically anxiety. A correlational research design was used to understand the relationship between anxiety and the learning environment. Two anxiety tests on online and on-site learning were administered to 16 chemistry students receiving English for Specific Purposes courses. Thus, the current research findings revealed that there is no significant difference in the students’ levels of anxiety whether learning online or in the traditional classroom. These findings necessitate future implications of applying practical techniques and strategies to reduce anxiety in both learning environments to create a suitable and supportive atmosphere that works for better comprehensible input for university students.